Before Tomorrowland - Jensen, Jeff; Bird, Brad, 1957- (Disney Press, 2015)
"Based on the spellbinding world of the Walt Disney Studios film, Tomorrowland, this original prequel novel features a 20-page comic book and unlocks a place of unfathomable science and technology and the famous people behind it. The year is 1939. A secret society of extraordinary geniuses is about to share an incredible discovery with the world. A misguided enemy - half man, half machine - will stop at nothing to prevent the group from giving this forbidden knowledge to humanity. And a mother and son on vacation in New York City are handed a comic book infused with a secret code that will lead them straight into the crossfires of the conspiracy" --Publisher's website.